Gender differences in the association between weight-adjusted waist index and migraine: A cross-sectional study. - Shulong Liu; Jiangting Li; Guobo Xie (PLoS ONE)
Objective This study examines how weight-adjusted waist index (WWI) correlates with the occurrence of migraine in U.S. adults. Background Being overweight significantly increases the likelihood of experiencing migraines; nonetheless, conventional metrics like waist circumference (WC) and body mass index (BMI) might not completely capture the level of migraine risk tied to obesity. WWI integrates the strengths of WC while minimizing its correlation with BMI, which might make it a more accurate indicator of central obesity-related migraine susceptibility. Methods This study performed a cross-sectional analysis using data from 9,688 participants obtained from the National Health and Nutrition Examination Survey (NHANES), covering the years 1999-2004. Migraine occurrence was evaluated through questionnaires, and participants' WWI was computed. Weighted multivariable logistic regression models were used to examine the association between WWI and migraines. Restricted cubic splines (RCS) were applied to evaluate the dose-response relationship between WWI and migraines. Furthermore, interaction tests and subgroup analyses were executed. The receiver operating characteristic (ROC) curve, paired with DeLong et al.'s test, was employed to compare the predictive power of WWI, BMI, and WC for migraines. Results The overall prevalence of migraines was found to be 21.50% (weighted population: 31,888,075 out of 148,278,824). In Model 3, the link between WWI and migraines in women showed no statistical significance (OR = 0.94, 95% CI: 0.82-1.07). In this model, each unit increase in WWI among men was linked to a 22% higher risk of migraines (OR = 1.22, 95% CI: 1.05-1.42). When stratified by quintiles, individuals in the third quintile (Q3) displayed a 69% higher likelihood of experiencing migraines compared to those in the first quintile (Q1) (OR = 1.69, 95% CI: 1.19-2.40), with a significant inflection point observed at 10.95 cm/√kg. Significant interactions were noted among various age groups (p for interaction = 0.018). WWI demonstrated a stronger predictive capability for migraine compared to BMI and WC. Conclusion A U-shaped positive correlation of WWI with migraines was observerd among adult males in the U.S., while no significant correlation was found in females. Within the context of BMI and WC, WWI exhibited a superior predictive capacity for migraines.